Stevens–Johnson Syndrome and Toxic Epidermal Necrolysis Associated with Acetaminophen Use during Viral Infections - Ban, Ga-Young; Ahn, Seun-Joo; Yoo, Hye-Soo; Park, Hae-Sim; Ye, Young-Min (Immune network, 2016)
An association between drug treatment for viral infections and severe cutaneous adverse reactions has been noted. We investigated six patients diagnosed with Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) after being prescribed acetaminophen for suspected viral illnesses. Multiplex analysis was performed to measure cytokine levels in sera before and after treatment. IL-2Rα levels significantly decreased during the convalescence phase. Although acetaminophen is relatively safe, the drug can trigger SJS/TEN in patients with suspected viral infections. T-cells and monocytes may be key components of the link between viral infection and acetaminophen-induced SJS/TEN.